Comparing paper‐based and electronic multiple‐choice examinations with personal devices: Impact on students' performance, self‐efficacy and satisfaction. (2nd July 2018) - Nardi, Andrea; Ranieri, Maria
Abstract: Nowadays the size of university classes along with the growing number of students to be tested for final examination raise unprecedented challenges relating to the management, monitoring and evaluation of learning. Technology may provide some solutions that deserve to be investigated. This paper explores the potentialities and limitations of Computer‐Based Testing (CBT), specifically BYOD e‐test, compared to traditional Paper‐Based Testing (PBT) to verify whether, and to what extent, an electronic mode of assessment can become a suitable alternative to PBT. It is based on a study carried out at the University of Florence during 2016/17. 606 students participated in the study, of whom 443 opted for CBT using their own devices, while 163 preferred PBT. Participants who experienced CBT also answered a survey on perceptions, self‐efficacy and satisfaction. The results show that students' performances were better with CBT, and that a positive relationship exists between the perceived level of self‐efficacy and the propensity to adopt digital tests. In addition, students greatly appreciated the electronic system, especially for the possibility of immediate feedback. Some critical issues emerged relating to on‐screen reading, which suggests the need for careful design of testing tools.